2012
DOI: 10.1042/bj20120189
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM3 participates in the TGF-β1-induced epithelial–mesenchymal transition of human lens epithelial cells

Abstract: TGF-β (transforming growth factor-β)-induced EMT (epithelial-mesenchymal transition) induces the proliferation and migration of the HLE (human lens epithelial) cells. Ganglioside GM3, simple sialic-acid-containing glycosphingolipids on mammalian cell membranes, regulates various pathological phenomena such as insulin resistance and tumour progression. However, the relationship between ganglioside GM3 and TGF-β-induced EMT in the HLE B-3 cells is poorly understood. In the present study we demonstrated that gang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…Glycogenes inhibited when miR-200f levels are high ( Left , green arrow, red glycogenes) and promoted by loss of miR-200f ( Right , red arrow, green glycogenes) alter glycosylation in multiple contexts including receptor signaling (36), protein secretion (40), and cell-adhesion networks (2931). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycogenes inhibited when miR-200f levels are high ( Left , green arrow, red glycogenes) and promoted by loss of miR-200f ( Right , red arrow, green glycogenes) alter glycosylation in multiple contexts including receptor signaling (36), protein secretion (40), and cell-adhesion networks (2931). …”
Section: Discussionmentioning
confidence: 99%
“…MiR-200f is a regulatory component of the TGF-β EMT-signaling pathway, implying that B3GLCT, ST6GALNAC5 , and ST3GAL5 also are components of that pathway. Increased levels of the glycolipid GM3, the product of ST3GAL5 , have been shown to promote the dimerization and activation of TGF-β receptors (36). However, B3GLCT and ST6GALNAC5 are not known to be involved in EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Last, the metabolism of complex lipids and specifically glycosphingolipids has been shown to affect EMT. GM3 synthase converts lactosyl ceramide to a simple ganglioside called GM3 which is known to promote EMT by interacting with TGFβ receptors (275). It has been shown that ZEB1 can induce GM3 synthase gene by binding to its promoter and by repressing the micro-RNA mediated suppression of GM3 synthase in human lung cancer cells (122).…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…They also interact with well-known proteins such as EGFR2, TGFβ1R3, and VEGFR4 in various malignancies. GSLs are usually divided into two major families, known as galactosylated or glucosylated ceramides.…”
mentioning
confidence: 99%